2017
DOI: 10.3390/ijerph14060611
|View full text |Cite
|
Sign up to set email alerts
|

‘Hidden Habitus’: A Qualitative Study of Socio-Ecological Influences on Drinking Practices and Social Identity in Mid-Adolescence

Abstract: This study explored mid-adolescents’ views and experiences of socio-ecological influences on their drinking practices in order to help inform the development of interventions to reduce alcohol-related risk. We conducted 31 in-depth interviews with young people aged 13–17 in North East England. Verbatim interview transcripts and field notes were coded systematically and analysed thematically, following the principles of constant comparison. We adopted Bourdieu’s idea of social game-playing and elements of his c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 79 publications
1
18
0
Order By: Relevance
“…Bourdieu explains how individuals engage in certain consumption practices to influence their position, for instance by consuming a specific product or having a certain drinking behaviour (Bourdieu, 1984 ). Along those lines, Scott et al used Bourdieu’s concepts to highlight how different forms of alcohol consumption helped construct adolescents’ identity (Scott, Shucksmith, Baker, & Kaner, 2017 ). Bourdieu furthermore underlines how one group’s alcohol habitus is shaped through distinction to the practices of other groups.…”
Section: Methodsmentioning
confidence: 99%
“…Bourdieu explains how individuals engage in certain consumption practices to influence their position, for instance by consuming a specific product or having a certain drinking behaviour (Bourdieu, 1984 ). Along those lines, Scott et al used Bourdieu’s concepts to highlight how different forms of alcohol consumption helped construct adolescents’ identity (Scott, Shucksmith, Baker, & Kaner, 2017 ). Bourdieu furthermore underlines how one group’s alcohol habitus is shaped through distinction to the practices of other groups.…”
Section: Methodsmentioning
confidence: 99%
“…While qualitative studies have reported the effect of peer, parental and wider cultural influences on young people’s drinking, interaction and engagement with social networking sites (SNS) and the integral nature of the social context,13–15 29–32 few recent qualitative studies have involved an in-depth examination of social and cultural influences on the initiation and escalation of alcohol use during early-adolescence to mid-adolescence in England, and the interaction between such behavioural influences. We sought to obtain data on social influences that would be applicable to the national context to inform development of preventive interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of studies, young people highlighted the joy they experienced when eating unhealthy food [59,60] and drinking alcohol [55,61,62,63,64]. Certain foods and snacks were most enjoyable (“ For each night five days in a row you probably would get Snickers, Twix, bag a chips, and a soda, and probably a night for every day that week.…”
Section: Resultsmentioning
confidence: 99%